Epoxy Vitrimer Based on Temperature‐Responsive Pure Organic Room Temperature Phosphorescent Materials. Issue 10 (10th March 2022) - Wu, Peng; Lou, Lingyun; Xu, Tianqi; Zhao, Jianming; Hai, Mingtan; Wang, Dong; Cao, Hui; He, Wanli; Yang, Zhou
Abstract: Pure organic room temperature phosphorescent (RTP) materials are introduced to polymer matrices in recent researches for their attractive properties like mechanical character, low cost, facile fabrication and so on. Besides, polymers are considered to provide a rigid environment for phosphors to reduce nonradiative pathways and achieve efficient RTP emission. Vitrimers are new thermosetting polymers with dynamic covalent bond networks and temperature‐depended topology structure changes. Herein we report a rational design strategy for tailoring intermolecular interactions to enhance room temperature phosphorescence from purely organic materials in amorphous vitrimer matrices at ambient conditions. Unlike conventional polymer‐based phosphorescent materials, vitrimer matrices show not only rigid environment and optical transparency but thermal dynamic characteristics. A temperature‐responsive phosphorescent system of small phosphor DTPA‐CZ and vitrimer matrices is obtained, with a phosphorescence lifetime of 1.025 s and a photoluminescence efficiency up to 78.7 %. Abstract : Polymer‐based pure organic phosphorescent materials show great potential in display, bioimaging, anti‐counterfeiting fields. This work combines carbazole derivative phosphor (DTPA‐CZ) with epoxy vitrimer to achieve efficient and long afterglow phosphorescence emission. Vitrimer matrix affect the photoluminescence properties of DTPA‐CZ and enhance the phosphorescence emission prominently by repressing the nonradiative decay. The dynamic covalent bond within vitrimer embodies this phosphorescent material thermal‐responsive properties to design a temperature control switch judged by detecting the afterglow time.